Understanding leadership behavior during team crisis for outsourced project / Nur Shafizah Shahriman - Shahriman, Nur Shafizah (2017)
The research is to understand leadership behavior during team crisis for outsourced project. There are two types of leadership behavior which are task oriented behaviour and relationship oriented behavior. These types of behavior are applied by project manager to handle outsourced project. Outsourced project is a combination of internal and vendor entities, but the research only studied from vendor entity because the successful of the project depends on capabilities of the vendor, to solve any problems occurs during managing outsourced project. There are several types of outsourced project such as system development, network management and desktop management, but this research only focus on outsourced system development project. System development has different phases, but this research only focus on requirement and design phase. This is because at these phases, intensity discussion among team member is increased, which can lead to team crisis. There are several types of team crisis such as knowledge, communication, information and technology crisis but, this research only studied of knowledge and communication crisis because these two crises play an important role as a serve to ensure the smooth implementation of the outsourcing project. The problem arises when transferring knowledge from client to vendor, and absence of effective communication line between project manager with team project. The research is split into two phases which is Literature Review, and gathered information from case study. The first phase is to acquire knowledge by reading the various sources including books, journal, websites and articles to gain the understanding of leadership behavior during team crisis for outsourced project. The second phase is, the information was gathered by conducting interview session with project manager who managed the outsourced system development project. There is difference information gathered between Literature Review and case study. From literature review, project manager used leadership styles depending on performance readiness of team member based on Situational Leadership Model (SLM) but for case study, project manager used leadership styles depending on the types of the outsourced project. The information gathered is analyzed in order to construct a conceptual leadership behavior model during team crisis for outsourced project. The outcome of this research is a conceptual leadership behavior model is to assist project manager to react appropriately based on these types crisis when it occurred.